Meta-analyses of cognitive functions in early-treated adults with phenylketonuria. (December 2022) - Romani, Cristina; Olson, Andrew; Aitkenhead, Lynne; Baker, Lucy; Patel, Dhanesha; Spronsen, Francjan Van; MacDonald, Anita; Wegberg, Annemiek van; Huijbregts, Stephan
Abstract: Our study estimated size of impairment for different cognitive functions in early-treated adults with PKU (AwPKU) by combining literature results in a meta-analytic way. We analysed a large set of functions (N = 19), each probed by different measures (average = 12). Data were extracted from 26 PKU groups and matched controls, with 757 AwPKU contributing 220 measures. Effect sizes (ESs) were computed using Glass' ∆ where differences in performance between clinical/PKU and control groups are standardized using the mean and standard deviation of the control groups. Significance was assessed using measures nested within independent PKU groups as a random factor. The weighted Glass' ∆ was − 0.44 for all functions taken together, and − 0.60 for IQ, both highly significant. Separate, significant impairments were found for most functions, but with great variability (ESs from −1.02 to −0.18). The most severe impairments were in reasoning, visual-spatial attention speed, sustained attention, visuo-motor control, and flexibility. Effect sizes were larger with speed than accuracy measures, and with visuo-spatial than verbal stimuli. Results show a specific PKU profile that needs consideration when monitoring the disease. Highlights: This is the largest meta-analysis of cognitive deficits in adults with PKU to date. Significant impairments compared to control are shown for most functions. The profile of deficits is disease-specific. Some functions are severely impaired, others are spared or weakly impaired. The level of impairment (overall EF = −0.44) calls for treatment improvements.